AN OUTLOOK ON POWER VACUUMS IN THE POLITICAL SPECTRUM - Dahiya, Usha (International Journal of Research -GRANTHAALAYAH, 2025)
When a great power’s control over a region wanes, other states often compete to occupy the political space and assert their influence in that area. Building on this conventional wisdom, policymakers have long warned against the dangers of creating power vacuums—such as through reducing international commitments—and have advised against it whenever possible. Concerns about power vacuums have been a prominent feature in high-level U.S. strategic discussions for years. Notably, in 1972, President Nixon from the USA told Mao Zedong, “in international relations there are no good choices. One thing is sure – we can leave no vacuums.” Recently, the debate over the implications of power vacuums has resurfaced, especially as discussions intensify about the U.S. strategy in response to a rising China. Proponents of continued global engagement argue that significant retrenchment would create a power vacuum likely to be filled by adversaries, thereby jeopardizing national security.